(untitled) (Baghdad Science Journal, 2018)
Thin films of CdTe were prepared with thickness (500, 1000) nm on the glass substrate by vacuum evaporation technique at room temperature then treated different annealing temperatures (373,473,and 573)K for one hour. Results of the Hall Effect and the electrical conductivity of (I-V) characteristics were measured in darkness and light.at different annealing temperature results show that the thin films have ability to manufacture solar cells, and found that the efficient equal to (2.18%) for structure solar cell (Algrid / CdS / CdTe /glass/ Al) and the efficient equal to (1.12%) for structure solar cell (Algrid / CdS / CdTe /Si/ Al) with thick ness of (1000) nm with CdTe thin films at RT.